Analysis of the Influence Theory off Planned Behavior on Interest in Money Waqf (Case Study in Dompet Dhuafa Republika) - Doni Priambodo (Jurnal Ilmiah Ekonomi Islam, 2022)
Abstract Cash waqf can be in the form of cash waqf given from the wakif to the institution receiving the cash waqf. This research aims to analyze the effect of Theory of Planned Behavior (Attitudes, Norms and Behavioral Control) on the interest of waqif in waqf money with a case study at the Dompet Dhuafa Republika Waqf Institute. The strategy of gathering information in this investigation was through the delivery of questionnaires to the wakif as many as 105 respondents. The information collected was analyzed using the Structural Equation Modeling approach with the AMOS program. The results obtained are that there is a positive and significant influence between behavioral and normative factors on interest in waqf for cash waqf, while the behavioral control variable has no positive and fundamental effect on interest in cash waqf. This paper is expected to provide benefits for cash waqf management institutions in understanding the behavior of waqf in cash waqf so that it can be used as a guide in advancing procedures for collecting cash waqf funds. Keywords: Cash Waqf, Theory Plannned of Behavior JEL Classification: Management and Cash Waqf